Cytoskeleton as a roadmap navigating rhizobia to establish symbiotic root nodulation in legumes - Hlaváčková, Kateřina; Šamaj, Jozef; Ovečka, Miroslav (Biotechnology advances, 2023)
Legumes enter into symbiotic associations with soil nitrogen-fixing rhizobia, culminating in the creation of new organs, root nodules. This complex process relies on chemical and physical interaction between legumes and rhizobia, including early signalling events informing the host legume plant of a potentially beneficial microbe and triggering the nodulation program. The great significance of this plant-microbe interaction rests upon conversion of atmospheric dinitrogen not accessible to plants into a biologically active form of ammonia available to plants. The plant cytoskeleton consists in a highly dynamic network and undergoes rapid remodelling upon sensing various developmental and environmental cues, including response to attachment, internalization, and accommodation of rhizobia in plant root and nodule cells. This dynamic nature is governed by cytoskeleton-associated proteins that modulate cytoskeletal behaviour depending on signal perception and transduction. Precisely localized cytoskeletal rearrangements are therefore essential for the uptake of rhizobia, their targeted delivery, and establishing beneficial root nodule symbiosis. This review summarizes current knowledge about rhizobia-dependent rearrangements and functions of the cytoskeleton in legume roots and nodules. General patterns and nodule type-, nodule stage-, and species-specific aspects of actin filaments and microtubules remodelling are discussed. Moreover, emerging evidence is provided about fine-tuning the root nodulation process through cytoskeleton-associated proteins. We also consider future perspectives on dynamic localization studies of the cytoskeleton during early symbiosis utilizing state of the art molecular and advanced microscopy approaches. Based on acquired detailed knowledge of the mutualistic interactions with microbes, these approaches could contribute to broader biotechnological crop improvement.
Keywords: mikrotubuly; Symbiosis; Legumes; Rhizobium; Actin filaments; cytoskelet; Signalling; Microtubules; Fabaceae; symbióza; Nodules; Rhizobia; Root hairs; Cytoskeleton